PERSPECTIVES OF PERCEIVED ORGANIZATIONAL SUPPORT (POS) THEORY TOWARDS INDIVIDUAL HAPPINESS - Sam, Toong Hai; Isa, Khairunesa; Palpanadan, Sarala Thulasi; Xiao Ping, Wang (2024)
Introduction: Organizations must take a proactive stance when it comes to their workers' welfare and well-being to demonstrate their best commitment in this regard. Objective: This paper presents the descriptive data of organizational factors that contribute to staff happiness in one of the Malaysian Technical University Network (MTUN) clusters in Malaysia. Methods: This study was conducted at one of the Malaysian Technical University Network (MTUN) clusters in Malaysia. It involved 20 respondents comprising academicians who had served more than 11 years. The session at the Round Table Discussion was organized to discuss the issues that were highlighted in the survey data. Results and Conclusion: Analysis showed that the personal economy and personal appreciation dimension were among the highest contributors in determining employee happiness, followed by a support system, workstation environment, and trust. Furthermore, the discussion is related to the general aspect of Perceived Organizational Support Theory which supports the data analysis on individual happiness aspect in the institution of higher education. Originality/Value: By emphasizing the role of factors such as support systems, workstation environment, and trust in determining employee happiness, the study provides valuable insights into the broader dynamics of the workplace. Understanding how these factors influence employee satisfaction can inform strategies for improving organizational culture and employee engagement. Hence, this finding is related to Sustainable Development Goal (SDG) 3: Good Health and Well-being because it focuses on individual happiness, which is closely tied to mental well-being and overall health, both of which are central to SDG 3.